Effect of Shell-Curvature and Geometric Nonlinearity on Stress Concentration in Composite Thin-Shell Panels Having a Central Square Hole and Subject to Uniaxial Tension Loading - Abu-Farsakh, Ghazi; Al-Rosan, Sora (Jordan Journal of Civil Engineering, 2019)
In this paper, the distribution of stresses in an open circular cylindrical thin-shell panel having a central square hole and various shell curvatures and is subject to uniform axial tension loading is investigated. Analysis is carried out using both linear and geometrically nonlinear behaviors using the finite element analysis computer program ABAQUS. Shell panels are assumed to consist of four symmetrical laminas [θ/-θ]s that are made of a fibrous Graphite/Epoxy (AS/3501) composite. Fiber-orientation angles varied from θ= 0⁰ to 90⁰ in steps of 15⁰. Three types of shell curvatures are considered; namely, shallow shell (SS), moderately-deep shell (MDS) and deep shell (DS) with all edges being clamped. The presence of a central hole resulted in the redistribution of stresses along the hole perimeter. Accordingly, this changed the general trend of stresses from tension to compression in the hole zone and caused stress concentration at hole corners. Also, the peak stresses are increased due to increasing the shell curvature. Type of finite element analysis showed a small effect on shell stresses. In geometrically nonlinear analysis, stresses are decreased and stress redistribution becomes more uniform than that corresponding to linear analysis. Moreover, stress concentration factors (SCFs) are slightly affected due to type of analysis.